Funciones ejecutivas del adulto mayor de la comunidad de Ulpan, Cantón Chambo - Peñafiel Parra, Briggete Carolina (2022)
The main objective of this research was to determine how executive functions affect the elderly in the community of Ulpan, Canton Chambo. This problem was important since the executive functions are a series of higher cognitive capacities that allow the channeling of information, planning, decision-making, and control of emotions; Older adults with a deterioration in executive functions have greater complexity when performing different activities, which causes their performance to drop. The methodology used was a mixed approach. Concerning the qualitative approach, the design was ethnographic; in the quantitative approach, its design was non-experimental due to its level it was descriptive, the type of research by objective was primary, due to time, it was transversal due to the place was field research, the population was the elderly from the community of Ulpan, Cantón Chambo, the sample was intentional non-probabilistic, of 22 older adults. The techniques used were: the application of the Mini-Mental Test Folsten on the dependent variable and an interview in the independent variable, which was a source of great help for obtaining and collecting data and results, which indicate that there is a mild to moderate cognitive impairment in most of the sample, identifying attention as one of the executive functions with a lower performance at the level presented by each one of them.